Situating Feminism, Patent Law, and the Public Domain - Foster, Laura A. (Columbia Journal of Gender and Law, 2011)
Both critical intellectual property studies and feminist legal scholarship seldom address the gendered dimensions of patent law or its implications for women and women’s rights. This lack of attention raises awareness of the need to broaden our approach to studies of patent law and the public domain. During recent fieldwork in South Africa, I began to consider patent law as a feminist site of inquiry and to think through the difficulties of such an examination. Khomani San women in the northern Cape express concerns over the patenting of biological and genetic materials derived from their indigenous traditional knowledge. Maintaining control over their knowledge and resources is important for feeding their families and safeguarding their intellectual histories and heritage as female plant gatherers. The Khomani San peoples are currently engaged in political struggles against patent law and the ownership of their indigenous knowledge, but such organizing has not been explicitly gender-based. Although some Khomani San women articulate patent law as a women’s rights issue, other women in the community consider issues of patent law to be gender-neutral. Concerns arising from patent ownership of indigenous knowledge are also not the main priority. Khomani San women committed to gender-based political organizing explain the difficulties of mobilizing and educating indigenous San women in their communities. Political organizing takes money and resources, and San communities are spread out over great distances within South Africa, Botswana, and Namibia, making meetings difficult to arrange. Issues of patent law are also not as significant or pressing as the material conditions of domestic violence, substance abuse, and poverty facing San women and their families right now. Thus, Khomani San men and women are involved in struggles against patent law, yet their political work does not explicitly address the connections between patent ownership and gendered social relations.